2015
DOI: 10.1007/s10803-015-2673-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Friendship Quality of Children with Autism Spectrum Disorder as Compared to their Peers in Mixed and Non-mixed Dyads

Abstract: There has been limited research exploring the similarity of perception of friendship quality between children with Autism Spectrum Disorder (ASD) and their friends. In this study, 45 children with ASD participated together with their friends. Two levels of friendship quality congruency were investigated: reciprocity and mutuality. A high proportion of the friendships were reciprocated for both the mixed and non-mixed friendship groups. Nevertheless, students with ASD reported substantial differences in percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…The only researchers to date to collect in-depth reciprocity and mutuality data from friend dyads that include a person with autism are Petrina et al (2016). This group examined the congruency of perception in relation to mutuality and reciprocity in the established friend dyads of children with autism (mean age was 8.45 years).…”
Section: Reciprocity In Friendshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The only researchers to date to collect in-depth reciprocity and mutuality data from friend dyads that include a person with autism are Petrina et al (2016). This group examined the congruency of perception in relation to mutuality and reciprocity in the established friend dyads of children with autism (mean age was 8.45 years).…”
Section: Reciprocity In Friendshipmentioning
confidence: 99%
“…Although the methods used to collect reciprocity data were similar (though not exactly the same) as the previous research studies that included reciprocity data (Chamberlain et al, 2007;Kasari et al, 2011;Rotheram-Fuller et al, 2010) in contrast to previous research, these researchers found that best friendships were more frequently reciprocated, but still less reciprocated than those friendships where neither child has an ASD diagnosis. Petrina et al (2016) also reported differences in perceptions of the friendship quality, based on analysis of responses on the Friendship Quality Questionnaire (Parker & Asher, 1993), specifically with respect to the extent to which disagreements were resolved, the quality and quantity of disclosure of personal information, as well as the feelings/emotions between the friends in the dyad. These researchers concluded, based on their data, that children with autism may have different perceptions of friendships than their partners, and that because of this future research should consider the perceptions of both members of the friend dyad.…”
Section: Reciprocity In Friendshipmentioning
confidence: 99%
“…Petrina and colleagues examined friendship congruency in children with ASD. 3 They investigated reciprocity of friendship via friend nomination in both ASD-only and ASD/neurotypical mixed groups. The majority of friendships across both groups were reciprocated (89%).…”
Section: Child Factors That May Influence Development Of Relationshipsmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is characterized by social communication challenges and restricted, repetitive, and/or intense behaviors or interests that have the potential to impact social, communication, motor, play, and cognitive skills. Many studies indicate that individuals with ASD have difficulty building and maintaining relationships, 1 have poorer quality friendships than neurotypical children, 2,3 and present with isolation and loneliness. 4,5 Given these factors, interventions have often focused on increasing the social interaction and social communication skills of children with ASD, with a view toward collateral benefits for relationships and friendships.…”
mentioning
confidence: 99%
See 1 more Smart Citation